Mapping the Terrain of Islamic Social Enterprise: A Comprehensive Literature Review - Wali Saputra (Jurnal Teologi Islam, 2025)
The objective of this research endeavor is to systematically delineate and scrutinize the extant corpus of literature pertaining to Islamic Social Enterprise (ISE), with the intention of elucidating predominant themes, frameworks, methodological orientations, and discernible research lacunae within the domain. A Systematic Literature Review (SLR) methodology was employed, encompassing an examination of 65 peer-reviewed scholarly articles published from the year 2000 to 2025, derived from databases such as Scopus, Web of Science, and Google Scholar. Rigorous inclusion and exclusion criteria were implemented, succeeded by bibliometric and thematic analysis facilitated by PRISMA and qualitative synthesis methodologies. The findings of this investigation indicate a burgeoning scholarly interest in ISE, particularly within the past decade, with prevailing themes encompassing waqf-based enterprises, zakat-driven empowerment initiatives, and hybrid business models congruent with maqashid shariah principles. Notwithstanding its nascent importance, the domain remains disjointed, characterized by a dearth of empirical substantiation, absence of standardized governance frameworks, and inadequate engagement with digital innovation. Furthermore, the literature predominantly features qualitative methodologies, largely concentrated in Southeast Asia, notably in Malaysia and Indonesia. The review is confined to publications in the English language and may not comprehensively encapsulate grey literature or non-indexed regional scholarship. Future investigations should integrate quantitative impact evaluations, cross-national comparative analyses, and the incorporation of digital technologies in the enhancement of ISE development. This study presents the inaugural comprehensive and structured synthesis of ISE literature, proposing a conceptual framework and delineating a future research agenda to promote the evolution of Islamic Social Enterprises as a distinct paradigm of ethical and faith-based social innovation.